PENERAPAN ALGORITMA APRIORI UNTUK PENENTUAN STRATEGI MARKETING PENJUALAN PRODUK - Mohammad Badrul (LPPM STMIK ANTAR BANGSA, 2015)
Abstract—Each company or organization that wants to survive needs to determine an appropriate marketing strategy. Data sales of products made by the company will eventually generate mountains of data. products offered various brands, brand influence people to buy the product, to determine the brand with the highest sales priori algorithms needed to know, and with the help of tools Tanagra, products with the highest sales can be known. Priori algorithms including the type of association rules in data mining. One association analysis phase which attracted the attention of many researchers to produce efficient algorithms is the analysis of patterns of high frequency (frequent pattern mining). Important or not an association can be identified by the two benchmarks, namely: support and confidence. Support (support value) is the percentage of the combination of these items in the database, while confidence (value certainty) is a strong relationship between the items in the rules of association. Priori algorithm can be helpful for the development of marketing strategies.